Докажите тождество(а^3*b^3-1)^3-(1+a^3*b^3)^3+6a^6*b^6=-2

Докажите тождество (а^3*b^3-1)^3-(1+a^3*b^3)^3+6a^6*b^6=-2
Гость
Ответ(ы) на вопрос:
Гость
[latex](a^3*b^3-1)^3-(1+a^3*b^3)^3+6a^6*b^6=-2[/latex] решаем левую часть [latex](a^3*b^3-1)^3=a^9b^9-3a^6b^6+3a^3b^3-1[/latex] [latex](a^3*b^3+1)^3=a^9b^9+3a^6b^6+3a^3b^3+1[/latex] [latex]a^9b^9-3a^6b^6+3a^3b^3-1-a^9b^9-3a^6b^6-3a^3b^3-1+6a^6*b^6 =[/latex] [latex]-6a^6*b^6-2+6a^6*b^6=-2[/latex] -2=-2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы